Amelioration of endotoxin-induced sepsis in rats by membrane anchored lipid conjugates - Beck, Grietje; Hermes, Wilhelm-Clothar; Yard, Benito A.; Kaszkin, Marietta; Zabern, Detlef von; Schulte, Jutta; Haak, Markus; Prem, Katharina; Krimsky, W.; Ackern, Klaus van; Woude, Fokko J. van der; Yedgar, Saul (Critical care medicine, 2003)
OBJECTIVE: In the pathogenesis of septic shock, caused by either bacterial toxins or trauma, increased production of multiple proinflammatory mediators, such as phospholipase A(2) (PLA(2)), cytokines, and chemokines, is known to be of major importance. The present study was undertaken to investigate the influence of a newly designed extracellular PLA(2) inhibitor (ExPLI) on synthesis of proinflammatory mediators and mortality rate in a rat sepsis model. DESIGN: Prospective, randomized animal study. SETTING: Experimental laboratory. SUBJECTS: Male Wistar-rats weighing 200-300 g. INTERVENTIONS: Mortality was induced by intraperitoneal bolus administration of lipopolysaccharide 15 mg/kg in 22 rats that were pretreated with NaCl or ExPLI (150 mg/kg). Furthermore, nine rats received a sublethal bolus of lipopolysaccharide (7.5 mg/kg) and nine rats received lipotechoic acid (8 mg/kg) simultaneously with or after ExPLI administration. Blood samples were collected from these rats, and cytokine concentrations were assessed by enzyme-linked immunosorbent assay. Lung and kidney were removed for RNA isolation and immunohistological analysis. MEASUREMENTS AND MAIN RESULTS: ExPLI treatment significantly reduced lipopolysaccharide-induced mortality of rats (90.9 and 36.4%, p <.05). Up-regulation of tumor necrosis factor-alpha and interleukin-6 production in serum after endotoxin treatment was significantly inhibited when ExPLIs were administered at the time of or before sepsis induction by using lipopolysaccharide or lipotechoic acid (p <.01). Similarly, messenger RNA expression of secreted PLA(2)-IIA, interleukin-1, or inducible nitric oxide synthase and the expression of intercellular adhesion molecule-1 were significantly down-regulated in lung and kidney of ExPLI-treated rats, as demonstrated by RNase protection assay, reverse transcription-polymerase chain reaction, or immunohistochemistry. CONCLUSIONS: ExPLIs may be considered as potentially effective compounds to prevent the production of inflammatory mediators and to improve mortality rate in septic patients.